Echocardiographic predictors of thrombus in left atrial appendage—The role of novel transthoracic parameters - Kaufmann, Damian; Wabich, Elżbieta; Kapłon-Cieślicka, Agnieszka; Gawałko, Monika; Budnik, Monika; Uziębło-Życzkowska, Beata; Krzesiński, Paweł; Starzyk, Katarzyna; Wożakowska-Kapłon, Beata; Wójcik, Maciej; Błaszczyk, Robert; Hiczkiewicz, Jarosław; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction The left atrium appendage thrombus (LAAT) formation is a complex process. A CHA2DS2-VASc scale is an established tool for determining the thromboembolic risk and initiation of anticoagulation treatment in patients with atrial fibrillation or flutter (AF/AFL). We aimed to identify whether any transthoracic echocardiography (TTE) parameters could have an additional impact on LAAT detection. Methods That is a sub-study of multicenter, prospective, observational study LATTEE (NCT03591627), which enrolled 3,109 consecutive patients with AF/AFL referred for transesophageal echocardiography (TEE) before cardioversion or ablation. Results LAAT was diagnosed in 8.0% of patients. The univariate logistic regression analysis [based on pre-specified in the receiver operating characteristic (ROC) analysis cut-off values with AUC ≥ 0.7] identified left ventricular ejection fraction (LVEF) ≤ 48% and novel TTE parameters i.e., the ratios of LVEF and left atrial diameter (LAD) ≤ 1.1 (AUC 0.75; OR 5.64; 95% CI 4.03–7.9; p < 0.001), LVEF to left atrial area (LAA) ≤ 1.7 (AUC 0.75; OR 5.64; 95% CI 4.02–7.9; p < 0.001), and LVEF to indexed left atrial volume (LAVI) ≤ 1.1 (AUC 0.75, OR 6.77; 95% CI 4.25–10.8; p < 0.001) as significant predictors of LAAT. In a multivariate logistic regression analysis, LVEF/LAVI and LVEF/LAA maintained statistical significance. Calculating the accuracy of the abovementioned ratios according to the CHA2DS2-VASc scale values revealed their highest predictive power for LAAT in a setting with low thromboembolic risk. Conclusion Novel TTE indices could help identify patients with increased probability of the LAAT, with particular applicability for patients at low thromboembolic risk.